KEABSAHAN JUAL BELI KENDARAAN BERMOTOR TANPA DISERTAI SURAT KEPEMILIKAN - Anastasia Pricillia Wibowo (Fakultas Hukum Universitas Narotama, 2022)
The sale and purchase agreement is the most widely used agreement for the legal transfer of ownership. in the legal system, the transaction form, consequences and legal protection are clearly regulated for the parties. It is urgent to establish juridical provisions to protect the parties from various negative and exploitative actions that are detrimental to the seller and the buyer. All types of property can be traded, as long as there are no rules prohibiting it, both in the form of movable and immovable objects. One of the objects of the transaction is motorcycles, both new and used, financial ability usually affects people's purchasing power because not all of them can afford to buy a new motorcycle because the price is quite high. So as an alternative, some people buy second-hand motorcycles, both those that are half-used, and those that are old, according to their wishes, needs, and financial capabilities. Keywords: Buying and selling, legitimacy, motorized, ownership certificate